Optimization of the Preparation of Gelatin Hydrolysates with Antioxidative Activity from Lizardfish (Saurida spp.) Scales Gelatin - Sutee Wangtueai (Science Faculty of Chiang Mai University, 2019)
The enzymatic hydrolysis of fish-scale gelatin using papain to obtain hydrolysate preparations with antioxidant properties was optimized using response surface methodology (RSM). The optimized parameters included enzyme-to-substrate ratio, reaction temperature and hydrolysis time. The optimal conditions for high antioxidant activity were 3% enzyme-to-substrate ratio, reaction temperature of 55°C, and hydrolysis time of 3 h. The RSM model gave predicted values of 61.7% for the 2, 2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, 485 mM Trolox/g for the 2, 2’-azinobis[3-ethylbenzothiazoline-6-sulfonic acid] (ABTS) radical scavenging activity, and 9.2 mM Fe2SO4.7H2O/g of fish-scale gelatin hydrolysates (FSGH) for the ferric reducing antioxidant power (FRAP) assay. This was corroborated by verification experiments under optimal conditions which gave an estimated degree of hydrolysis (DH) of 73.3±0.5, DPPH radical scavenging activity of 64.1±0.9%, an ABTS radical scavenging activity of 480±1 mM Trolox/g, and a FRAP value of 9.1±0.1 mM Fe2SO4.7H2O/g of FSGH. The functional properties of FSGH were determined. The solubility was evaluated over a wide pH range of 2-10, which had a value with the range of 80-94%. The foam expansion and foam stability were evaluated with 0.5% concentration of FSGH. The FSGH had 8.67% foam expansion and 2.0-6.7% foam stability. In addition, the FSGH had a 3.45% emulsion centrifugation stability (ECS) and a 0.73% emulsion thermal stability (ETS).